Rhino-orbital-cerebral mucormycosis in acute myeloid leukemia patients: a case series from Sri Lanka - Pradeep Siriwardena; Ushani Wariyapperuma; Pasindu Nanayakkara; Naamal Jayawardena; Dhanushka Mendis; Milhan Bahar; Buddhika Somawardana (BMC Infectious Diseases)
Abstract Background Mucormycosis, is a rare yet potentially life-threatening fungal infection common in immunocompromised patients. Despite optimal care, mucormycosis in haemato-oncological patients often results in poor outcomes. This case series details the presentations and unique challenges faced during the management of patients with acute myeloid leukemia who developed rhino-cerebral mucormycosis. Case presentation We present three cases of rhino-cerebral mucormycosis in patients with acute myeloid leukemia: two females aged 35 and 29, and one male aged 42. Symptoms manifested during chemotherapy induction, with all patients experiencing symptoms suggestive of rhino, orbital, or cerebral infection in a background of severe neutropenia (ANC < 0.5). Nasal endoscopy revealed necrotic tissue in all cases, with contrast-enhanced computer tomography (CECT) confirming invasive fungal infection. Rhizopus species were isolated in cultures from the two female patients, and histopathological evidence of fungal invasion was noted in one. Prompt treatment with liposomal Amphotericin B combined with surgical debridement with functional endoscopic sinus surgery (FESS) and treatment of neutropenic sepsis resulted in the survival of two patients, though one succumbed during treatment. Conclusions This case series highlights the importance of early clinical suspicion and treatment of mucormycosis in hematological malignancies. Due to mild and atypical presentations and lack of confirmation by microbiological and histological methods, a multifaceted diagnostic approach combining clinical, laboratory, and imaging modalities is essential. A multidisciplinary treatment approach with the management of concomitant complications like neutropenic sepsis is crucial for better outcomes.